2016
DOI: 10.22555/pjets.v5i2.904
|View full text |Cite
|
Sign up to set email alerts
|

The Estimation ofAggregate Consumption Function for High Income Countries

Abstract: <span>Aggregate Real Private Consumption (ARPC) is one of the major components of the Gross <span>Domestic Product (GDP)that contributes to specify any economy’s long term living standards. The <span>contribution of ARPC stands on an average around 55%. It is therefore important to understand the <span>components of the consumption which is almost more than half of the aggregate economic expenditure. <span>The study is an attempt to make a case for developing countries to bring po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Meanwhile, in the long-run, values of MPC out of the real GDP for Australia, Korea, New Zealand, and Singapore are 0.579, 0.640, 0.650, and 0.629, respectively, implying that a 1% increase in real GDP would cause consumption to increase by 0.579, 0.640, 0.657 and 0.629 respectively (Ahmed et al, 2015). These results are very close to the value of the global MPC constant estimate of 0.66.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, in the long-run, values of MPC out of the real GDP for Australia, Korea, New Zealand, and Singapore are 0.579, 0.640, 0.650, and 0.629, respectively, implying that a 1% increase in real GDP would cause consumption to increase by 0.579, 0.640, 0.657 and 0.629 respectively (Ahmed et al, 2015). These results are very close to the value of the global MPC constant estimate of 0.66.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the average propensity to consume (APC) is the fraction of income devoted to consumption. According to Keynes, for every increase in income, the APC declines (Ahmed et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the past research paid attention to older methodologies that did not consistently provide reliable findings. Ahmed et al (2015) used an Autoregressive distributed lag approach to estimate the absolute income hypothesis (AIH) and permanent income hypothesis (PIH) in Korea, Singapore, Australia, and New Zealand. They concluded that unemployment and interest rates have significant short-run impacts on household consumption, but wealth and income possess considerable long-run effects.…”
Section: Introductionmentioning
confidence: 99%